Kecerdasan Interpersonal dan Perilaku Prososial - M. Fiky Tartila; Lailatuzzahro Al-Akhda Aulia (Ilmu Psikologi Universitas Yudharta Pasuruan, 2021)
Prosocial includes all forms of action taken or planned to help others without seeing of the helper's motives. Many factors can influence prosocial, one of which is interpersonal intelligence. This study uses a quantitative research method with a comparative causal model. The sample in this study was 50 employees who were taken using a purposive sampling technique. Data collection in this study used the interpersonal intelligence scale and the prosocial scale. The data analysis used regression. From the results of data analysis obtained Freg of 0.2153 with Ftab 5% 0.279. Thus it can be concluded that there is no relationship between interpersonal intelligence and prosocial.